GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1547 species occurrences available in GBIF matching the query: TaxonKey: Oeceoclades maculata (Lindl.) Lindl.. The dataset includes 1547 records from 116 constituent datasets: 5 records from JOI - Herbário Joinvillea. 2 records from HUEM - Herbário da Universidade Estadual de Maringá. 13 records from HUFU - Herbarium Uberlandense. 4 records from Phanerogamic Botanical Collections (S). 4 records from PRECIS (KwaZulu-Natal Herbarium). 1 records from University of Vienna, Institute for Botany - Herbarium WU. 1 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 4 records from Census of the flora of Benin. 10 records from IAC - Herbário do Instituto Agronômico de Campinas. 8 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 30 records from Naturalis Biodiversity Center (NL) - Botany. 3 records from SPSF - Herbário Dom Bento José Pickel. 9 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 3 records from PRECIS. 1 records from SPF - Herbário da Universidade de São Paulo. 34 records from UFP - Herbário UFP - Geraldo Mariz. 5 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from HERBAM - Herbário da Amazônia Meridional. 1 records from ICN - Herbário do Instituto de Ciências Naturais. 2 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 54 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 7 records from Museu Paraense Emilio Goeldi Herbarium. 6 records from CESJ - Herbário Leopoldo Krieger. 1 records from OUPR - Herbário "Professor José Badini". 27 records from Plantae of Costa Rica (INBio). 3 records from Herbier du Bénin. 17 records from MBM - Herbário do Museu Botânico Municipal. 9 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 108 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Australia's Virtual Herbarium. 38 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 4 records from Plantas Bosque Seco Chicamocha. 1 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 4 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 10 records from iNaturalist Research-grade Observations. 3 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 4 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 29 records from ALCB - Herbário Alexandre Leal Costa. 6 records from HUSC - Herbário Unisanta. 1 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 1 records from VIC - Herbário da Universidade Federal de Viçosa. 1 records from EFC - Herbário Escola de Florestas Curitiba. 30 records from ASE - Herbário da Universidade Federal de Sergipe. 27 records from UEC - Herbário da Universidade Estadual de Campinas. 13 records from FUEL - Herbário da Universidade Estadual de Londrina. 1 records from Jardin botanique de Montréal (JBM). 5 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 2 records from Herbaria of the University and ETH Zürich. 162 records from Tropicos Specimen Data. 20 records from Natural History Museum (London) Collection Specimens. 2 records from Natural History Museum, Vienna - Herbarium W. 18 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 4 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 3 records from Formación del banco de datos del herbario (UCAM). 39 records from NMNH Extant Specimen and Observation Records. 8 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 2 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 24 records from MEXU/Plantas Vasculares. 1 records from Herbarium Berolinense. 2 records from HBGSpermatophyta - Herbarium Hamburgense. 4 records from Harvard University Herbaria. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 8 records from CVRD - Herbário da Reserva Natural Vale. 21 records from USF Herbarium. 2 records from Field Museum of Natural History (Botany) Seed Plant Collection. 56 records from MBML-Herbario - Herbário Mello Leitão. 20 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 1 records from MISS_DC_01MAR2006. 2 records from Sukkulentensammlung Zürich. 1 records from Herbarium Senckenbergianum (FR). 1 records from University of Ghana - Ghana Herbarium. 1 records from Herbario Amazónico Colombiano. 2 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 4 records from UPCB - Herbário do Departamento de Botânica. 1 records from HURB - Herbário do Recôncavo da Bahia. 4 records from Geographically tagged INSDC sequences. 3 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 1 records from Herbarium togoense. 8 records from HVASF - Herbário Vale do São Francisco. 8 records from HST - Herbário Sérgio Tavares. 64 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 8 records from FURB - Herbário Dr. Roberto Miguel Klein. 1 records from HUEG - Herbário da Universidade Estadual de Goiás. 25 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1 records from CNMT - Herbário Centro Norte Mato Grossense. 39 records from UFPB - Herbário Lauro Pires Xavier - (JPB). 28 records from EAC - Herbário Prisco Bezerra. 42 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 12 records from R - Herbário do Museu Nacional. 86 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 4 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 1 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 31 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 44 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1 records from Wilson Botanical Garden - Las Cruces Biological Station. 17 records from UB - Herbário da Universidade de Brasília. 1 records from Central African Plants. 5 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 3 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 4 records from SysTax - Botanical Gardens. 31 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 7 records from African Plants - a photo guide. 7 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 10 records from EAN - Herbário Jaime Coelho de Moraes. 2 records from SysTax - Herbaria. 16 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 17 records from Geneva Herbarium – General Collection (G). 25 records from Instituto de Botánica Darwinion. 4 records from SJRP - Herbário de São José do Rio Preto. 2 records from Herbario Virtual Bosques Secos de Colombia - Sección Herbario Universidad de Córdoba (HUC). 3 records from UFMT - Herbário UFMT. 3 records from CPAP - Herbário CPAP. 2 records from HEPH - Herbário Ezechias Paulo Heringer. 5 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 6 records from MOSS - Herbário Dárdano de Andrade Lima. 2 records from UESC - Herbário Universidade Estadual de Santa Cruz. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences